2014
DOI: 10.1159/000365034
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Efficiency of Infant Formulae: A Review

Abstract: Breast-fed and formula-fed infants differ in terms of nutrient intake, growth, and metabolic and endocrine responses. The energetic efficiency, i.e. the weight or length gain per 100 kcal of energy intake, of breast-fed infants is about 11% higher than the energetic efficiency of formula-fed infants. Only limited data is available on the influence of formula composition on the energetic efficiency of infant formulae. We conducted a review of controlled trials to identify the impact of the macronutrient composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
12
1
Order By: Relevance
“…The Davis Area Research on Lactation, Infant Nutrition, and Growth (DARLING) study observed increased FFM and total weight gain associated with HP intake at 3, 6, 9, and 12 months of age, with protein intake estimated from food records in breastfed and formula‐fed infants. In the same study, FFM gain and total weight gain per gram of protein intake were higher in breastfed infants than in formula‐fed infants , indicating a higher feed efficiency . Other studies also found higher FM (not FFM) in breastfed infants throughout the first year .…”
Section: Discussionmentioning
confidence: 67%
“…The Davis Area Research on Lactation, Infant Nutrition, and Growth (DARLING) study observed increased FFM and total weight gain associated with HP intake at 3, 6, 9, and 12 months of age, with protein intake estimated from food records in breastfed and formula‐fed infants. In the same study, FFM gain and total weight gain per gram of protein intake were higher in breastfed infants than in formula‐fed infants , indicating a higher feed efficiency . Other studies also found higher FM (not FFM) in breastfed infants throughout the first year .…”
Section: Discussionmentioning
confidence: 67%
“…Formula-fed infants have a slightly higher energy intake (by 15-18%) than those breastfed (Fig. 4) [21], which is related to a higher energy cost for growth (lower energetic efficiency) in formula-fed infants [22,23]. In contrast to the relatively small difference in energy intake, conventional formula feeding provides 55-80% more crude protein intake, calculated on the basis of total nitrogen intake [24].…”
Section: Translational Application Of Research Results Into Practicementioning
confidence: 99%
“…2 ) [34] . We consider this an important mechanism by which the protein quality provided to infants significantly modifies the energetic efficiency of infant formulae for weight and length gain [35] . Therefore, not only lowering protein quantity but also improving protein quality in infant feeding may provide benefits for growth and health, a concept that deserves further evaluation.…”
Section: Metabolic Response To Infant Protein Supply and Impact On Grmentioning
confidence: 99%